ผลกระทบของมาตรการ Work from Home ที่มีต่อการปฏิบัติงานพัฒนาทรัพยากรบุคคล กรณีศึกษาการประปานครหลวง - ชวิศา เสาวจันทร์ (จุฬาลงกรณ์มหาวิทยาลัย, 2022)
This research investigated the impact of Work from Home (WFH) policy on performance of human resource development (HRD): Case study of a Metropolitan Waterworks Authority (MWA). This study used a mixed method consisting of quantitative and qualitative research methods. The study collected data by using a questionnaire with 29 HRD employees of MWA and collected data by In-depth interview with 4 HRD employees of MWA. The objectives of this research are as follows; 1. To study impact of WFH policy on performance of HRD: Case study of MWA. and 2. To provide policy recommendations to WFH policy. In this research, the HRD procedures are divided into three parts: 1. Analysis and Design 2. Development and Implementation and 3. Evaluation. The results of quantitative research are as follows; Impact of WFH policy to performance of each part are not different. The impact of WFH policy on performance of HRD was low-level in all parts. However, the average points from raw data of each part are slightly different which is consistent with the results of the qualitative research. The perspectives and opinions of interviewees are in the same direction. From in-depth interviews, the impact of WFH policy to performance of HRD in each part are different. Sorts descending order are as follows; First is the analysis and design parts. Second is the development and implementation parts. The last is the evaluation part.